Near-infrared reflectance and thermal insulating performance of Mo-doped Bi2WO6 with 3D hierarchical flower-like structure as novel ceramics pigment. Issue 8 (1st June 2020) - Tian, Mengmeng; Yao, Lingyun; Han, Aijun; Zhu, Xufei; Chen, Chenlu; Ye, Mingquan; Chen, Xin
Abstract: The pigments with the formula of Bi2 W1− x Mo x O6 ( x  = 0.0, 0.1, 0.2, 0.3, 0.4) are synthesized by one step hydrothermal method. The pigments are characterized with XRD, FE-SEM, XPS, UV/VIS/NIR spectrometer, thermal conductivity and TG-DTA. The results reveal that the samples are of orthorhombic phase with no impurity phase existing and three-dimensional hierarchical flower-like architectures with diameter ranging from 2 to 3 μm. The color of the doped samples progressively transfers from pale yellow to yellow. The band gap decreases from 2.82 eV to 2.42 eV, which is attributed to the charge transfer excitation changes from Bi 6s → O 2p to the transition of Mo 3d → O 2p. As compared with the conventional pigments with similar color, the Mo-doped Bi2 WO6 pigments perform better on the near-infrared solar reflectivity and the highest near-infrared solar reflectance is as high as 80.80%. The distinction of the NIR solar reflectance values among the pigments is majorly attributed to the different oxygen concentration induced by the reaction formula: Bi2 Mo1- x W x O6 → Bi2 Mo1- x W 6+ x- δ (W 6+ ·2e) δ O6-δ + δ 2 O 2 ↑.The thermal conductivity of some Mo-doped Bi2 WO6 pigments is apparently lower than its pigment counterpart owning to the 3D hierarchical flower-like structure. The pigments are also possessing eminent thermal and chemical stability. The Mo- doped Bi2 WO6 samples not only have high near-infrared reflectance with beautiful color but also have comparatively benign thermal insulating performance, so that they are promising to be served as novel amiable ceramic pigments to manipulate the thermal property of ceramic materials.